Evidence of d-wave superconductivity in K1−xNaxFe2As2 (x=0,0.1) single crystals from low-temperature specific-heat measurements - Mohamed, Mahmoud; Grinenko, V.; Aswartham, S.; Morozov, I.; Roslova, M.; Vakaliuk, O.; Johnston, S.; Efremov, D. V.; van den Brink, J.; Rosner, H.; Kumar, M.; Hess, C.; et al. (Physical review. B, Condensed matter and materials physics, 2013)
From the measurement and analysis of the specific heat of high-quality K1−xNaxFe2As2 single crystals we establish the presence of large T2 contributions with coefficients αsc≈30 mJ/mol K3 at low T for both x=0 and x=0.1. Together with the observed √B behavior of the specific heat in the superconducting state both findings give evidence of d-wave superconductivity on almost all Fermi-surface sheets with an average gap amplitude of Δ0 in the range of 0.4-0.8 meV. The derived Δ0 and observed Tc agree well with the values calculated within Eliashberg theory, adopting a spin-fluctuation mediated pairing in the intermediate coupling regime.
Im Titel ist "1-x", "x" und "2" tiefgestellt
Gesehen am 04.05.2021